2019
DOI: 10.1002/best.201900019
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung des Zug‐ und Verbundverhaltens von Basaltfaserverstärkter Kunststoff‐Stabbewehrung in Beton

Abstract: Bei der Instandsetzung von Stahlbetonbauteilen muss, um die Dauerhaftigkeit sicherzustellen, die Betondeckung hinreichend groß gewählt werden. Der Einsatz alternativer Bewehrungsmaterialien wie z. B. Basalt als Faserverbundstab bietet durch die Korrosionsbeständigkeit gegenüber Karbonatisierung und Chlorideinwirkung die Möglichkeit, die Betondeckung zur Sicherstellung der Dauerhaftigkeit zu minimieren und gleichzeitig korrosionsresistente Bauteile zu erstellen. Nachfolgend werden – als Auszug aus einem Forschu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
2
2
0
1
Order By: Relevance
“…The maximum bond stressed could be reached at a slip value of s = 0.5 mm. The obtained test results for the BFRP reinforcement bars correspond to the documented test results of e. g Kampmann et al[41] (τb,max / √fcm = 3.08), Wolf et al[42] (τb,max / √fcm = 2.55), Hao et al[43] (τb,max / √fcm = 2.45) or El Refai et al[44](τb,max / √fcm = 2.45), where similar BFRP reinforcement was tested in pull-out tests. In addition, Model Code 2010[23] defines the bond stress to τbm = 1.8 • fctm and τb,max = 2.5•√fc for bond lengths five times the diameter (lb = 5 • Ø), which also corresponds to the obtained experimental results (see Table2).…”
supporting
confidence: 87%
“…The maximum bond stressed could be reached at a slip value of s = 0.5 mm. The obtained test results for the BFRP reinforcement bars correspond to the documented test results of e. g Kampmann et al[41] (τb,max / √fcm = 3.08), Wolf et al[42] (τb,max / √fcm = 2.55), Hao et al[43] (τb,max / √fcm = 2.45) or El Refai et al[44](τb,max / √fcm = 2.45), where similar BFRP reinforcement was tested in pull-out tests. In addition, Model Code 2010[23] defines the bond stress to τbm = 1.8 • fctm and τb,max = 2.5•√fc for bond lengths five times the diameter (lb = 5 • Ø), which also corresponds to the obtained experimental results (see Table2).…”
supporting
confidence: 87%
“…The maximum bond stressed could be reached at a slip value of s = 0.5 mm. The obtained test results for the BFRP reinforcement bars correspond to the documented test results of e. g Kampmann et al[41] (τb,max / √fcm = 3.08), Wolf et al[42] (τb,max / √fcm = 2.55), Hao et al[43] (τb,max / √fcm = 2.45) or El Refai et al[44](τb,max / √fcm = 2.45), where similar BFRP reinforcement was tested in pull-out tests. In addition, Model Code 2010…”
supporting
confidence: 87%
“…Test ID Material Finally, the relaxation rate is calculated using Equation (1) with σ(t) being the calculated remaining stress after the final calculation step according to Equation (5). For multiple creep tests conducted by Wang et al, 26 Shi et al 25 showed that the relaxation rates calculated in this manner are in good agreement with the experimentally determined relaxation rates from actual relaxation tests on the same type of FRP reinforcement.…”
Section: Sourcementioning
confidence: 84%
“…1 Thus, those structures have to be repaired or replaced prematurely. To address this issue, a wide variety of investigations on fiber-reinforced polymer (FRP) reinforcement have been carried out, including past and current research projects, focusing on different types of reinforcement fibers such as carbon, 2,3 basalt, 4,5 or glass 6,7 and the work of standards committees and general literature. [8][9][10] Due to favorable properties like their high tensile strength, low weight, and high resistance against corrosion, FRP reinforcement can be a viable alternative for regular steel Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%